2022
DOI: 10.3390/antiox11050850
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging Effect of 4-N-Furfurylcytosine in Yeast Model Manifests through Enhancement of Mitochondrial Activity and ROS Reduction

Abstract: Small compounds are a large group of chemicals characterized by various biological properties. Some of them also have antiaging potential, which is mainly attributed to their antioxidant activity. In this study, we examined the antiaging effect of 4-N-Furfurylcytosine (FC), a cytosine derivative belonging to a group of small compounds, on budding yeast Saccharomyces cerevisiae. We chose this yeast model as it is known to contain multiple conserved genes and mechanisms identical to that of humans and has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Moreover, yeasts and especially the budding yeast S. cerevisiae are very often used as eukaryotic cell models to study stress response, aging mechanisms and specific cellular effects of pro-and antioxidant molecules. In these studies, several different tests are used to assess either the oxidative stress level or the antioxidant power of molecules added to fight this stress (see for examples [28][29][30][31]). The most commonly used method is exposing yeast cells to a strong oxidant agent such as H 2 O 2 , and the most classical read-out for their response is a simple viability test: yeast cells are plated on a solid-agar-rich growth medium and incubated at 28 • C for 72 h, and finally colonies formed are counted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, yeasts and especially the budding yeast S. cerevisiae are very often used as eukaryotic cell models to study stress response, aging mechanisms and specific cellular effects of pro-and antioxidant molecules. In these studies, several different tests are used to assess either the oxidative stress level or the antioxidant power of molecules added to fight this stress (see for examples [28][29][30][31]). The most commonly used method is exposing yeast cells to a strong oxidant agent such as H 2 O 2 , and the most classical read-out for their response is a simple viability test: yeast cells are plated on a solid-agar-rich growth medium and incubated at 28 • C for 72 h, and finally colonies formed are counted.…”
Section: Discussionmentioning
confidence: 99%
“…This points to the fact that FC's anti-aging activity is through the inhibition of TOR signaling pathway. 40 Gentirigeoside B and gentiopicroside Gentirigeoside B is a triterpenoid glycoside isolated from the Chinese traditional medicinal plant Gentiana rigescens Franch. Xiang, L., et al reported that gentirigeoside B significantly extended both the replicative and chronological lifespan of yeast.…”
Section: -N-furfurylcytosinementioning
confidence: 99%